PENGARUH MENONTON SIARAN ACARA DR. OZ INDONESIA DI TRANS TV TERHADAP PENGETAHUAN KESEHATAN MASYARAKAT DI DESA KOTABUNAN KABUPATEN BOLAANG MONGONDOW TIMUR - Sulistyo, Bayu Tri; Mewengkang, Norma N.; Londa, Jeffry W. (ACTA DIURNA KOMUNIKASI, 2015)
The influence of watching a broadcast of the show Dr. Oz Indonesia at Trans tv To Public Health Knowledge in Kotabunan Village East Bolaang Mongondow Regency. The research was based on a theory of Stimulus-Organism-Response theory and Cultivation theory. The purpose of this research was to prove the effects of mass media on society. The research method used is descriptive statistics are purely quantitative, i.e. the approach done by calculation or data analysis in statistics to describe the influence of the free variables, namely watching a broadcast of the show Dr. Oz Indonesia (X) against variables bound i.e. health knowledge (Y). Data analysis technique used is a simple linear regression obtained results of Y ' = 26.694 + 0.462 X shows the Constants of 26.694 stated that if the variable X is considered constant or equal to zero (0) then the Variable Y is of 26,694. Results of correlation Coefficient 0.434 or 4.34%, this means that the influence of the variable X against Y variables are classified in the category of being. whereas the determination of the koefisisien gets the value of R2 = 0.188. This indicates that the variable Y got influences from variable X of 18.8 %, while the remainder (100% -18.8% = 81.2 %) is explained by other reasons. Test results showed the value of t thitung > ttabel 3.910 > 1.997 so or Ho denied and Ha received, meaning significant. So, watch the broadcast of the show Dr. Oz Indonesia Trans tv in effect significantly to public health knowledge. Keywords: Watch, media impact, health knowledge